2019
DOI: 10.1590/0034-737x201966010007
|View full text |Cite
|
Sign up to set email alerts
|

Growth, water consumption and basil production in the hydroponic system under salinity

Abstract: In irrigated crops, salinity is the main cause of the reduction of growth and productivity, with damage of the variability according to the sensitivity of the crop. The objective of this work was to evaluate the growth, water consumption and production of basil cv. Toscano Folha de Alface under saline stress, in different frequencies of recirculation of the nutritive solution and hydroponic systems. The experimental design was a completely randomized design, in a factorial scheme 3 x 2 + 1, where the first fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…A sensibilidade às concentrações de sais pode variar de acordo com o genótipo de cada planta, algumas são mais resistentes e outras apresentam pouca resistência (SOUZA et al, 2010). Santos et al, (2019) mostrou que o excesso de sais no cultivo hidropônico de manjericão reduz o crescimento da planta e este tipo de estresse compromete a produção desta espécie principalmente no nordeste do Brasil. Maciel et.…”
Section: Resultsunclassified
“…A sensibilidade às concentrações de sais pode variar de acordo com o genótipo de cada planta, algumas são mais resistentes e outras apresentam pouca resistência (SOUZA et al, 2010). Santos et al, (2019) mostrou que o excesso de sais no cultivo hidropônico de manjericão reduz o crescimento da planta e este tipo de estresse compromete a produção desta espécie principalmente no nordeste do Brasil. Maciel et.…”
Section: Resultsunclassified
“…under different hydroponic conditions. Walters and Currey (2015) and Santos et al (2019) found no significant differences for growth variables and production of basil under cultivation in the hydroponic systems NFT and DFT. The use of marginal quality water, such as brackish water, increased the yield of essential oil in the basil genotypes 'Grecco a Palla' (Gondim Filho et al, 2018) and 'Gennaro de Menta' (Azevedo Neto et al, 2019;Silva et al, 2019).…”
mentioning
confidence: 87%
“…The NFT hydroponic system is characterized by frequent circulation of the nutrient solution, generally with short intervals of 15 min. The DFT system has a layer of nutrient solution that remains in constant contact with the roots, as such, the plants do not undergo any water restriction, which means the interval time between the circulation of the nutrient solution can be extended, as has been shown by various authors (Silva et al, 2016;Silva et al, 2018;Santos et al, 2019;Silva et al, 2020a).…”
Section: Experiments Design and Treatmentsmentioning
confidence: 99%
“…Regarding the first one, panels are floating in a container filled with nutrient solution (10-20 cm deep), while for the second, a nutrient solution flows from the upper end to the lower end and passes through troughs of about 10 cm placed on trays at a slope of 0.5-2%. Generally, the choice of the DFT or NFT hydroponic system does not lead to important changes under greenhouse conditions (Santos et al 2019). Nevertheless, DFT allowed an increase of 2.6 g in fresh weight of fresh basil compared to plants grown in NFT systems (Walters and Currey 2015).…”
Section: Hydroponicsmentioning
confidence: 99%